Social Well-Being and Related Factors in Students of School of Nursing and Midwifery - Alireza Salehi; Maryam Marzban; Maryam Sourosh; Farkhondeh Sharif; Mahmoud Nejabat; Mohammad Hadi Imanieh (Shiraz University of Medical Sciences, 2017)
Background: According to the World Health Organization viewpoint, social well-being is an important dimension of health along with physical and mental aspects. Evaluation of social well-being is necessary in students, especially in medical sciences students due to future responsibility as health care professionals. The present study attempted to investigate the level of social well-being, five domains of it (like actualization, integration, contribution), and some related factors in the school of nursing and midwifery students. Methods: This cross-sectional study was carried out between Julys to December 2015 and comprised 346 students in the school of nursing and midwifery in Shiraz University of Medical Sciences, Shiraz, Iran. Social well-being, socio-demographic status and physical activity were measured by valid questionnaires. Univariate linear regression analysis, multiple imputation method, ANOVA and independent sample t-test were used as different statistical methods. The P values less than 0.05 were considered as statistically significant. Results: The mean score of social well-being was 50. The minimum and maximum scores of social well-being were 20 to 100. Married students had higher social well-being than single students in univariate linear regression (Beta: 2.111, 95% CI: (0.387 to 3.738), P=0.017). Also, social integration had higher scores in married students (P=0.015). Social actualization was higher in male students (P=0.015); on the other hand, social contribution was higher in female students (P=0.026). Conclusion: The results of our study showed that social well-being status of students in this research was not satisfactory. Designing and conducting programs for promotion of social well-being, for example preparing facilities for marriage of students, can be helpful. Evaluation of social well-being in students of other schools with multicenter studies seems to be useful.